Ex-UUM director named Kuin rector - The, Star (The Star, 2013)
ALOR SETAR: Former Universiti Utara Malaysia (UUM) City Campus director Prof Datuk Mohd Yusof Kasim has been appointed the new rector of the problem-ridden Kolej Universiti Insaniah (Kuin).